Pengembangan Sistem Informasi Pencatatan dan Pemantauan Distribusi Surat Masuk dan Surat Keluar dengan Pendekatan Berorientasi Objek (Studi Kasus : Detasemen A Pelopor Satbrimob Polda Jatim) - Wika Vidi Aryasworo; Ismiarta Aknuranda; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Detasemen A Pelopor Satbrimob Polda Jatim is the operational executive element in Satuan Brimob Polda Jawa Timur which is handling over high intensity security disturbance. Like an organization, Detasemen A Pelopor Satbrimob Polda Jatim has letter management activities. During this time the management of the letter in Detasemen A Pelopor Satbrimob Polda Jatim is still manually, causing some problems is difficult to do search for mail data, it is difficult to recap the letter data as a report. Besides it can not. From this it is necessary to improve the recording and dissemination activities of letters that have been running at this time by developing an Information System of Recording and Monitoring Distribution of Incoming and Outgoing Letter (SIPPDS) which can make it easier to record, store, search, reconcile letter data, and The task of mailing process on each part. In developing SIPPDS, researchers used a waterfall model, with an approach. The results of the research show on the design diagram, diagram, physical data model, and interface design. In the database. And MySQL database. While on a device that can be used properly, and try the compatibility that shows the system can be used properly on 9 types of web browsers.